METODE TAQRIR SEBUAH PENDEKATAN YANG MENYENANGKAN - Dicky Wirianto (Universitas Islam Negeri Ar-Raniry, 2012)
This article explains about taqrir (evidence) as an interesting approach in attempting a method in Islamic education. The utilizing of the taqrir method which is adopted from some Qurâ€™anic verses and text written in Arabic in BurhÄni model approach as being designed by al-Jabiri and subsequently being developed in variety of the educational theories both from al-Ghazali and John Dewey, the US educational figure, would be contexctually in its application as it integrates Islamic education and progressive educational model. The violence in education is frequent occurs if the method being applied is inappropriate. Thus, violence being conducted is through forcing the courses to the students, where he or she does not wish for studying. Consequently, the knowledge being transferred could not be rest on his or her heart.